The Australia Telescope 20 GHz Survey: the source catalogue - Murphy, T.; Sadler, E.; Ekers, Ronald; Massardi, M.; Hancock, Paul; Mahony, E.; Ricci, R.; Burke-Spolaor, S.; Calabretta, M.; Chhetri, R.; De Zotti, G.; Edwards, P.; et al. (Oxford University Press, 2010)
We present the full source catalogue from the Australia Telescope 20 GHz (AT20G) Survey. The AT20G is a blind radio survey carried out at 20 GHz with the Australia Telescope Compact Array (ATCA) from 2004 to 2008, and covers the whole sky south of declination 0?. The AT20G source catalogue presented here is an order of magnitude larger than any previous catalogue of high-frequency radio sources, and includes 5890 sources above a 20 GHz flux-density limit of 40 mJy. All AT20G sources have total intensity and polarization measured at 20 GHz, and most sources south of declination -15? also have near-simultaneous flux-density measurements at 5 and 8 GHz. A total of 1559 sources were detected in polarized total intensity at one or more of the three frequencies.The completeness of the AT20G source catalogue is 91 per cent above 100 mJy beam-1 and 79 per cent above 50 mJy beam-1 in regions south of declination -15?. North of -15?, some observations of sources between 14 and 20 h in right ascension were lost due to bad weather and could not be repeated, so the catalogue completeness is lower in this region. Each detected source was visually inspected as part of our quality control process, and so the reliability of the final catalogue is essentially 100 per cent. We detect a small but significant population of non-thermal sources that are either undetected or have only weak detections in low-frequency catalogues. We introduce the term Ultra-Inverted Spectrum to describe these radio sources, which have a spectral index a(5, 20) >+0.7 and which constitute roughly 1.2 per cent of the AT20G sample.